Fiscal Reform and Monetary Union in West Africa - Carsten Hefeker (Hamburg Institute of International Economics (HWWA), 2003)
The paper explores the interaction between the proposed monetary union for ECOWAS and structural reforms of fiscal policy. The effects depend to a large extent on the degree of similarity of member countries. In a monetary union of similar countries, member states run a more distortive fiscal policy, while their structural reform efforts will fall. This is also the case for countries that unilaterally peg to an anchor currency or introduce a foreign currency. In an monetary union with dissimilar countries the reverse can happen for those member states that are confronted with high distortion countries. This result implies that current WAEMU members will run a less distortive fiscal policy after the inclusion of other members of ECOWAS.
Keywords: F33; E61; E63; 330; West Africa; monetary union; fiscal policy; structural reforms; Finanzpolitik; Geldpolitik; Währungsunion; Konvergenzkriterien; Schätzung; ECOWAS-Staaten